AN INFORMATION RETRIEVAL APPROACH FOR ASSISTING USERS IN SOFTWARE ENGINEERING PROCESSES - Rodriguez, Guillermo (Interfaces Científicas - Exatas e Tecnológicas, 2018)
Documents written in natural language constitute a major part of the artifacts produced during the software engineering life cycle. There is a growing interest in creating tools that can assist users in all phases of the software life cycle. The assistance requires techniques that go beyond traditional static and dynamic analysis. An example of such a technique is the application of information retrieval (IR), which exploits information found in documents of a software engineering process. The increased availability of data created as part of the software development process allows managers to apply novel analysis techniques on the data and use the results to guide the project's stakeholders. These data are then used to predict defects, gather insight into a project's life-cycle, and other tasks. This work proposes an IR approach to assist users in software engineering processes according their profile. The approach consists in recommending them related documents to a retrieved one in order to users understand and follow the process in a correct way. Furthermore, the assistance concentrates on legacy systems in which engineers must acquire knowledge generated by others. Implementation of the approach and an overview of evaluation are also summarized.